2019
DOI: 10.1007/s11266-019-00158-9
|View full text |Cite|
|
Sign up to set email alerts
|

Between Collaboration and Subordination: State and Non-state Actors in Russian Anti-drug Policy

Abstract: Due to weak state and administrative capacity, the Russian government has involved resource-rich non-state actors into policymaking since about 2005 and established numerous institutionalized platforms, networks, and forums. These networks mainly emerge on regional and local levels and are designed to generate policy advice, implement decisions, and contribute to output legitimacy. A crucial question is how the authorities govern and regulate these bodies under the terms of a hybrid regime. The paper sheds lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We document a graduated approach of enrolling within the state system for policy innovations which ultimately led to the implementation of RH instruments. This insight is aligned with the perspective that the authoritarian state is not monolithicobserved from a close range, there are different centres of power and motivations for action (Aasland et al, 2020;Long, 2018). We enrich the understanding of a non-unitary state by explaining how a foundation strategically exploits such a situation for policy transfer.…”
Section: Discussionmentioning
confidence: 67%
“…We document a graduated approach of enrolling within the state system for policy innovations which ultimately led to the implementation of RH instruments. This insight is aligned with the perspective that the authoritarian state is not monolithicobserved from a close range, there are different centres of power and motivations for action (Aasland et al, 2020;Long, 2018). We enrich the understanding of a non-unitary state by explaining how a foundation strategically exploits such a situation for policy transfer.…”
Section: Discussionmentioning
confidence: 67%
“…Cluster 2 "Corporate social responsibility"; "Legitimacy"; "Russia" Firms legitimacy gaining: the CSR perspective Cluster 3 "Entrepreneurship"; "Firm performance" Entrepreneurial intensions for legitimacy gaining Cluster 4 "Institutional change"; "Regulation" Necessity of the specific regulation due to the institutional changes in a market The organizational legitimacy of Russian firms: Contextual specificity and legitimization strategies РЖМ 18 (3): 289-312 2020industry level [Karhunen, 2008], country level, and government level. In addition to the clusters recognized above, we identified one more research direction that focus on the specific policies of the government, helping to increase its legitimacy in Russia [Aasland, Kropp, Meylakhs, 2020]. For example, the authorities gain legitimacy by contributing into the public welfare, responding to some disasters, or collaborating with non-state actors in policy-making [Aasland, Kropp, Meylakhs, 2020;Fröhlich, Skokova, 2020;Mazepus, van Leeuwen, 2020].…”
Section: Domestic Market Focusmentioning
confidence: 99%
“…In addition to the clusters recognized above, we identified one more research direction that focus on the specific policies of the government, helping to increase its legitimacy in Russia [Aasland, Kropp, Meylakhs, 2020]. For example, the authorities gain legitimacy by contributing into the public welfare, responding to some disasters, or collaborating with non-state actors in policy-making [Aasland, Kropp, Meylakhs, 2020;Fröhlich, Skokova, 2020;Mazepus, van Leeuwen, 2020]. The first main focus of analyzed papers is the domestic market, especially Russian firms and their legitimacy within Russia (Appendix).…”
Section: Domestic Market Focusmentioning
confidence: 99%
“…While state—centric analyses have emphasized the capacity of non‐democratic regimes to control CSOs and suggested that civic space has been shrinking, a growing canon of critical work has pointed to the fact that civil society—state relations in non‐democratic settings are dynamic (Toepler et al., 2020). Instead of simply shrinking, civic space has been characterised by both expansion and contraction, opening in certain regards, and for certain purposes and actors, while closing for others (Aasland et al., 2020; Moldavanova et al., 2023). Additionally, research has demonstrated that the division of CSOs into advocacy organisations trying to promote democracy and service providing NGOs inevitably stabilising non‐democratic regimes is problematic.…”
Section: Introductionmentioning
confidence: 99%